The effects of alloying elements on the microstructure and annealing behavior of the twin-roll cast AA1050 strip - Karakoyun, Fatih. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
There are two main routes of sheet aluminum production DC casting and hot rolling route and continuous casting and cold rolling route. DC casting and hot milling route is the conventional way of production, the process is well known and controlled to maintain desired properties of the sheet. Continuous casting route includes twin belt casting, twin block casting and twin roll casting. All three processes are important in near net shape production. In twin belt casting and twin block casting, casting thickness is between 10 to 25mm. The produced sheet is not coilable sometimes, to eliminate this disadvantage tandem mills are adapted to the system that helps to produce coilable sheet. Twin-roll casting is a promising technology for sheet metal production. It was first developed for eliminating preheating and hot rolling operations in conventional sheet production. However it is cost effective and effective way of producing sheet metals, there are some problems in production and material quality such as heterogeneous microstructure. Because of the heterogeneous microstructure we can face problems in further forming operations after heat treatment. Because of heterogeneous microstructure and deformation, surface grains grow much more than the grains in the center. In this study effect of alloying elements on the microstructure and annealing behavior was investigated. A prototype twin roll caster was built in the Materials laboratory, by modifying the laboratory scale hot rolling machine. Some parts of the hot rolling machine was used; new casting rolls, housings for bearings and a twin roll casting tip was manufactured. Casting trials were utilized by this caster with different alloy content. The cast sheets were cold rolled and annealed to investigate the annealing behavior. Microstructures of as cast and annealed samples were investigated in terms of v optical microscopy. It was observed that however the grain size of samples from unmodified strip were larger than the modified strips, grain size after cold rolling and annealing was smallest and more equiaxed. Strontium was the most effective alloying addition in which the resultant microstructure of both the as cast and annealed samples were equiaxed and uniform through the thickness.
Keywords: Aluminum castings.; Metal castings.; Roll forming (Metalwork)